دور القروض الاستهلاكية في التنمية الاقتصادية - عدة, أميرة (My University, 2021)
This study aims to know the effective role played by consumer loans in economic development. These consumer loans have become the tool that is used to meet the needs of the community, and on the other hand, they are also used as a tool to encourage local production and the national market. By this method, you have contributed to supporting the national economy and moving the wheel of development Economic - Among the results of this study, we found that the agency of the Algerian People’s Loan Bank Mostaganem directs this type of loan, the lack of turnout by Algerian families due to the lack of culture in how to benefit from consumer loans. On the other hand, it became clear to me by conducting a field study for this agency that the bank has many clients Because of good dealings with customers key wor
بنك القرض الشعبي الجزائري CPA وكالة مستغانم
Keywords: القروض الإستهلاكية،التنمية الإقتصادية،القرض الشعبي الجزائري